Gender differences, routes of transmission, socio-demographic characteristics and prevalence of HIV related infections of adults and children in an HIV cohort from a rural district of India - Alvarez-Uria, Gerardo (PAGEPress Publications, 2012)
Despite 67% of HIV infected people in India are rural residents, the epidemiology of HIV in rural areas is not well known. This is an observational cohort study of 11,040 HIV infected people living in a rural district of India. The prevalence of hepatitis B, hepatitis C and syphilis of HIV infected patients were compared to the seroprevalence in 16,641 blood donors from the same area. The age of diagnosis in adults was below 35 years in 70% of cases and 56% were illiterate. One third of women were widows and only 3.6% of adults had a permanent job. Women were diagnosed at earlier age, had lower level of education, had poorer employment conditions and depended more on their relatives than men. In a survey performed to a subgroup of patients, 81% of women referred to have acquired HIV from their spouse, whereas 51% of men acquired HIV from commercial sex. Patients with HIV had significantly higher prevalence of hepatitis B, hepatitis C and syphilis than blood donors. Seroprevalence of HIV-2, hepatitis C and toxoplasmosis were low compared to other sites. Six percent were children (<15 years) and almost half of them had lost one or both of their parents. The study shows the poor socio-economical situation and the high level of illiteracy of people living with HIV in rural India, especially women. Future health programmes of HIV in India should take into account the particularities of the HIV epidemic in rural areas.